Symbol in translation - Jurewicz, Magdalena (Glottodidactica, 2016)
The subject for reflection in this paper is the translational challenge posed by the rendering of linguistic representations of national stereotypes, based on the example of the flower Edelweiss from the song Edelweiss which became a word-symbol for the inhabitants of the U.S.A. The translation of this stereotype created in the U.S.A., where the symbol of Edelweiss gained an added meaning, means that the translator of the English-German language pair is forced to explain the exo-cultural associations to those receivers who are enculturated in the country of this symbol’s origin.